Pengambilan Keputusan Perspektif Transdisipliner Manajemen di MAN 1 Padangsidimpuan - Nurapnilelawati Nurapnilelawati; Khairani Nasution; Nurika Khalila Daulay (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
The complexity of the educational problems experienced by our nation by our cannot be solved using one approach, but requires a transdisciplinary approach to solving problems. Transdiciplinarity is a collective approach that utilizes human knowledge and analytical skills to understand larger and more complex systems. The important meaning that marks transdiciplinarity is the process of integration of multidisciplines used to discuss issues or deal with problems. The implementation of transdisciplinary implies the existence of cooperative work or synergy between the people and the sectors involved in it. Transdisciplinary application is used to achieve something beyond the quantitative dimension. The existence of synergy in the transdisciplinary concept is intended to achieve a higher level of harmony than the integration of knowledge which is called a symphony. To find out how management transidisciplinary perspective decision making at MAN 1 Padangsidimpuan the author uses a qualitative descriptive research method. The instruments used in this study were observation. Interviews and documentation. The results of this study indicate that the head of madrasah, WKM, represents the teacher and the staff that the MAN 1 Padangsidimpuan has carried out decision-making, namely; 1. Decisions in a state of certainty, that is if all the information needed to make a decision is complete, then the decision is said to be in a state of certainty. In other words, when there is certainty, we can predict accurately the results of the action so that the decisions taken by the principal are right on target. 2. Decisions in the a state of risk, namely risk occors when the results of making a decision, even though it cannot be known with certainty, but the value of the possibility can be known. Asked for the views of the oldest, KTU and the Madrasah Head. 3. Decisions in a state of uncertainty is a situation where we cannot make a decision because it has never happened before (the first time), in this situation the head of MAN 1 Padangsidimpuan, if in making a decision on a problem that has never happened before, still conduct deliberation first with KTU and the madrasah head. 4. Decisions in a state of conflict sometimes decision making is not always smooth.